Clinical Course of Colorectal Carcinoma in a Developing Country - Muhammad Iqbal Khan, M Tariq Baqai , Haider Zaigham Baqai , MF Baqai (Journal of Rawalpindi Medical College, 2009)
Background: To study the clinical presentation of colo-rectal carcinoma in a developing country. Methods: In this non- interventional descriptive study, 75 patients were diagnosed to have color-rectal carcinoma in the eight years between November 1997 and December 2005. All the presenting features were recorded in a proforma. Detailed family history of gastro-intestinal or extra gastro-intestinal malignancy was obtained. Enquiry was made about the known risk factors of colo-rectal carcinoma. The information was analyzed to identify the common presenting features and role of known risk factors in the pathogenesis of disease. Results: Bleeding per rectum was the commonest presentation. However, surgical emergency was the second most common presentation in our study. The disease was found to be most common below fifty years of age. Rectosigmoid region (57%) was the commonest site. Histologically fifty perent of cases revealed well – differentiated morphology. Known environmental factors had no significant role in pathogenesis of the disease. Conclusion: Colorectal carcinoma is a disease of younger age in our society. Screening programs should include patients below 50 years of age.